Seleksi Penerimaan Programmer Menggunakan Simple Multi Attribute Rating Technique Method (SMART Method) dan Rank Order Centroid - Santoso, Hadi Irman (Journal of Information Technology, Software Engineering and Computer Science (ITSECS), 2024)
The problem is that programmers who do not have sufficient experience or skills can produce code that is of poor quality, difficult to maintain, and prone to bugs. The selection process for hiring programmers is a critical stage in building a competent and innovative software development team. This selection involves several stages, such as an assessment of understanding of basic programming concepts, problem-solving abilities, and technical skills relevant to the demands of the job. The purpose of this study is to combine the SMART and ROC methods in the selection of programmer acceptance, where the ROC method for determining the weight of criteria and the SMART method are used for ranking programmer selection candidates. The results of the programmer acceptance selection ranking combining the SMART and ROC methods provide an overview of rankings based on predetermined criteria and weights. The final score results of SMART and ROC then recommend rank 1 with a total score of 0.823 for Candidate C, rank 2 with a total score of 0.607 for Candidate A, rank 3 with a total score of 0.521 for Candidate D.